Morpho-anatomical evaluation of hypoglycaemic medicinal plants - Duarte Gondim, Roberta Sabrine; Ribeiro e Silva, Isolda; Freitas Soares Filho, Flávio; Silva Araújo Luz, Tássio Rômulo; Lopes de Castro, Tázia; Barreto Serra, Mariana; Assunção Barroso, Wermerson; Machado Vilanova, Crisálida (Scientia Plena, 2019)
This study aimed to morpho-anatomical characterize leaves of plants with hypoglycemic effect used by the Maracanã community of São Luís-MA. It was selected two vegetal species with lack of morpho-anatomical studies, which were Cissus verticillata (L.) Nicolson & C. E. Jarvis (Vitaceae) and Caesalpinia ferrea Mart. ex. Tul. var. leiostachya Benth (Leguminoceae). The botanic material was collected in the Dom Delgado University City, UFMA. It was realized paradermic and transverse sections free hand with blade support, using astra blue and basic fuchsin as colorants. The laminas were observed and photographed in optic microscopic. Cissus verticillata presented simple and opposite leaves, with membranous consistency, serrated margin, and acute top and cordate base. The mesophyll is dorsiventral composed by palisade and spongy parenchyma. Central rib with presence of reserve parenchyma and angular chollenchyma with some points of ring deposition. Caesalpinia ferrea presented smooth and simple leaves, uniseriate epidermis, curled cuticles and presence of stomata on both sides. Central rib with fundamental parenchyma composed by spherical cells and angular chollenchyma. The reported morphoanatomic characters of C. verticillata and C. ferrea leaves contribute to the identification and characterization of the quality of these vegetables, improving knowledge verification of plant species authenticity.